BAHASA FUNGSIONAL DI KEPOLISIAN REPUBLIK INDONESIA. SEBUAH KAJIAN : SEMANTIK - Marini Rehanisafira; Charlina Charlina; Elvrin Septyanti (Jurnal Guru Kita PGSD, 2021)
Abstract: Functional Language in the Indonesian National Police. A Study: Semantics. The purpose of this research is to (1) analyze the forms of functional language in the Indonesian National Police. (2) Analyzing Functional Language Function in the Police of the Republic of Indonesia. (3) Analyzing the Meaning of Functional Language in the Police of the Republic of Indonesia. The Approach Used In This Research Is Qualitative Research. The Method Used Is The Method To Listen, Record And Note. Listening and Recording Research Objects Are Done By Listening To The Language Used In The Police, In Other Words The Listening Method Using A Recorder. When observing written data, what the research does is read the entire contents of the required data repeatedly and then records the form, meaning and function of functional language. The technique of collecting data in this study is a note taking technique. Data Analysis Techniques In This Research Is To Identify, Classify, Analyze, Determine, Describe And Summarize The Form, Meaning And Function Of Functional Language In The Police Of The Republic Of Indonesia. Sources of data in this study are functional languages in the Indonesian National Police. Based on the research conducted by the author, it can be concluded that there are 2 forms of language in the functional language of the Police, namely the form of words and phrases. Word Form Consists Of 15 Data And Phrase Form Consists Of 71 Data. The meaning contained in the functional language of the police is the meaning of orders or directions in the functional language of the police. This Meaning is Analyzed Using the Meanings of the Terms in the Police Functional Language. Language Functions Available in Police Functional Languages , namely, MetalingualFunctions , Directive,FunctionsFunctions Interpersonal (Progmatics), andFunctions Referential.Keywords: Police Functional Language, Semantics Abstrak: Bahasa Fungsional di Kepolisian Republik Indonesia. Sebuah Kajian : Semantik. Tujuan Penelitian Ini Adalah Untuk (1) Menganalisis Bentuk-Bentuk Bahasa Fungsional Di Kepolisian Republik Indonesia. (2) Menganalisis Fungsi Bahasa Fungsional Di Kepolisian Republik Indonesia. (3)  Menganalisis Makna Yang Terdapat Pada Bahasa Fungsional Di Kepolisian Republik Indonesia. Pendekatan Yang Dipakai Dalam Penelitian Ini Adalah Penelitian Kualitatif. Metode Yang Digunakan Adalah Metode Simak, Rekam Dan Catat. Menyimak Dan Merekam Objek Penelitian Dilakukan Dengan Menyimak Bahasa Yang Dipakai Di Kepolisian, Dengan Kata Lain Metode Simak Rekam Menggunakan Alat Perekam. Saat Mengamati Data Tertulis, Yang Dilakukan Oleh Penelitian Adalah Membaca Keseluruhan Isi Data Yang Diperlukan Secara Berulangulang Kemudian Mencatat Bentuk, Makna Dan Fungsi Bahasa Fungsional. Teknik Pengumpulan Data Dalam Penelitian Ini Adalah Teknik Catat. Teknik Analisis Data Dalam Penelitian Ini Adalah Mengidentifikasi, Mengklasifikasi, Menganalisis, Menentukan, Memaparkan Dan Menyimpulkan Bentuk, Makna Dan Fungsi Bahasa Fungsional Di Kepolisian Republik Indonesia. Sumber Data Pada Penelitian Ini Adalah Bahasa Fungsional Di Kepolisian Republik Indonesia. Berdasarkan Penelitian Yang Dilakukan Oleh Penulis Dapat Disimpulkan Bahwa Bentuk Bahasa Yang Terdapat Dalam Bahasa Fungsional Kepolisian Ada 2 Bentuk Yaitu Bentuk Kata Dan Bentuk Frasa. Bentuk Kata Terdiri Dari 15 Data Dan Bentuk Frasa Terdiri Dari 71 Data. Adapun Makna Yang Terdapat Dalam Bahasa Fungsional Kepolisian Adalah Berupa Makna Pada Perintah Atau Arahan Dalam Bahasa Fungsional Kepolisian. Makna Ini Dianalisis Menggunakan Makna Istilah Yang Terdapat Dalam Bahasa Fungsional Kepolisian. Fungsi Bahasa Yang Terdapat Pada Bahasa Fungsional Kepolisian Yaitu, Fungsi Metalingual, Fungsi Direktif, Fungsi Interpersonal (Progmatik), Dan Fungsi Referensial.Kata Kunci: Bahasa Fungsional Kepolisian, Semantik